Optimization of process condition for extraction of gelatin from red tilapia skin (Oreochromis niloticus) by high pressure processing (HPP) - Yusof N.; Jaswir I.; Jamal P.; Jami M.S.; Octavianti F. (Universiti Putra Malaysia, 2024)
Indexed by SCOPUS